Quantum darwinism - Sheilla de Oliveira Marques (2020)
In this thesis, I present my work during my Ph.D. in quantum Darwinism. It is a original project, which has been peer-reviewed and accepted for publication in a respected international journal. In the first chapters, I recalled the essential concepts to understand quantum Darwinism, and in the two last, I present my works. The quantum Darwinism concept was constructed to explain a possible quantum-to-classical transition. My main interests are to find the quantum Darwinism implications in the system’s dynamics and to find more realistic models where it applies. The first work was finished and published while the second is still in progress. In the first model I studied quantum Darwinism in a many-body system of quantum harmonic oscillators where the subenvironments neither interact nor correlate between themselves. Through analytical and numerical calculations, we observed quantum Darwinism from two different approaches. We show quantum Darwinism through the BPH approach in a model for the first time. In contrast with a recently published work, we also show that quantum Darwinism can be observed even in a system with a high degree of non-Markovianity, and proposed a more suitable way to quantify it. In the second work, we investigate quantum Darwinism in a more realistic model where the subenvironments can become strongly correlated. The model consists of a two-level atom interacting with a fermionic environment and was used to study orthogonality catastrophe. As both orthogonality catastrophe and quantum Darwinism comes with decoherence, we are investigating if these two concepts are correlated. Beyond that, we chose this model because it can be mapped in a bosonic model of the Tonks-Girardeau gas enabling an experimental implementation with cold atoms. We are performing numerical and analytical calculations in this work. In the sixth chapter, I present the first result and describe what is missing.